2020
DOI: 10.1109/access.2020.2977258
|View full text |Cite
|
Sign up to set email alerts
|

Reliability-Based Safety Evaluation of Headlight Sight Distance Applied to Road Sag Curve Standards

Abstract: Sight distance is key to ensure safe road geometric design under all circumstances. Road design standards propose models simulating nighttime driving that contemplate the features of vehicle frontlighting systems to address the design of sag curves. These models are based on a deterministic approach, which is known to present a number of drawbacks. It neglects the stochastic nature of the variables involved and, therefore, no information is available about the safety margin of the design output. As opposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…In recent studies, the impact of the headlight beam features on headlight sight distance under such approaches was quantified (De Santos-Berbel et al, 2016). Moreover, variations of the vertical spread angle have been found to potentially produce a significantly different impact on safety (Andrade-Cataño et al, 2020).…”
Section: Nighttime Visibility and Glare Simulation On Highwaysmentioning
confidence: 99%
“…In recent studies, the impact of the headlight beam features on headlight sight distance under such approaches was quantified (De Santos-Berbel et al, 2016). Moreover, variations of the vertical spread angle have been found to potentially produce a significantly different impact on safety (Andrade-Cataño et al, 2020).…”
Section: Nighttime Visibility and Glare Simulation On Highwaysmentioning
confidence: 99%
“…where µ denotes the mean of the indicated random variable. Case 2: Substituting t' and v e ' from Equations ( 14) and ( 15) and d cir and t cir from Equations ( 11) and ( 12) into Equation ( 16), then substituting D 1 into Equation (27), the first derivatives of SM 1 with respect to v c , a, t c , and r can be derived as…”
Section: Distance Dmentioning
confidence: 99%
“…Case 3: Substituting t and d cir from Equations ( 5) and (11) into Equation ( 17), then substituting D 1 into Equation (27), the first derivatives of SM 1 with respect to v e , v c , a, t c , and r can be derived as…”
Section: Distance Dmentioning
confidence: 99%
See 1 more Smart Citation
“…They compared the accuracy and reliability of various estimation methods and provided recommendations for selecting the most appropriate method in different roadway design situations. In their study, Andrade-Cataño et al [ 32 ] applied a probabilistic approach to evaluate the risk level associated with sag curve designs and assessed the effect of variables involved in headlight sight distance (HSD) on the probability of noncompliance. The results showed that variables modelling headlight features significantly affect the risk level and that the risk associated with design outputs considered equivalent by the standard varies significantly.…”
Section: Introductionmentioning
confidence: 99%